2016
DOI: 10.20964/110402962
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processable P3HT/CdS Photodiodes and Their Electrical Characterization

Abstract: In this work we apply simple layer solution deposition methods for the assembling of CdS/P3HT (poly(3-hexylthiophene)) p-n heterostructures and analyzed their photodetection properties in the visible optical range. The CdS-n layers were deposited on ITO-coated glass substrates by the chemical bath method employing an ammonia-free recipe. The P3HT-p layers were deposited on the CdS/ITO/glass substrates by the casting method from solution by dissolving P3HT in chloroform. As the back electrodes, to complete the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In particular, in our group, we have reported a convenient ammonia-free CBD process to achieve CdS thin films [18,19], which have performed very well as window layers in solar cells, as well as active channels in TFTs employing organic (polyvinyl phenol-PVP), inorganic (SiO 2 and HfO 2 ) and hybrid (PVP-SiO 2 and PVP-TiO 2 ) dielectric gate layers [20][21][22][23]. We have also found that this CBD process can be photoactivated with UV light enabling the chemical deposition of CdS films at room temperature [22][23][24].…”
Section: Introductionmentioning
confidence: 86%
“…In particular, in our group, we have reported a convenient ammonia-free CBD process to achieve CdS thin films [18,19], which have performed very well as window layers in solar cells, as well as active channels in TFTs employing organic (polyvinyl phenol-PVP), inorganic (SiO 2 and HfO 2 ) and hybrid (PVP-SiO 2 and PVP-TiO 2 ) dielectric gate layers [20][21][22][23]. We have also found that this CBD process can be photoactivated with UV light enabling the chemical deposition of CdS films at room temperature [22][23][24].…”
Section: Introductionmentioning
confidence: 86%